An essential role for Bruton's [corrected] tyrosine kinase in the regulation of B-cell apoptosis. - Anderson, J S (1996)
Mutations of the Bruton's tyrosine kinase (btk) gene cause X-linked agammaglobulinemia (XLA) in humans and X-linked immune deficiency (Xid) in mice. To establish the BTK role in B-cell activation we examined the responses of wild-type and Xid B cells to stimulation through surface IgM and CD40, the transducers of thymus independent-type 2 and thymus-dependent activation, respectively. Wild-type BTK was necessary for proliferation induced by soluble anti-IgM (a prototype for thymus independent-type 2 antigen), but not for responses to soluble CD40 ligand (CD40L, the B-cell activating ligand expressed on T-helper cells). In the absence of wild-type BTK, B cells underwent apoptotic death after stimulation with anti-IgM. In the presence of wild-type but not mutated BTK, anti-IgM stimulation reduced apoptotic cell death. In contrast, CD40L increased viability of both wild-type and Xid B cells. Importantly, viability after stimulation correlated with the induced expression of bcl-XL. In fresh ex vivo small resting B cells from wild-type mice there was only barely detectable bcl-XL protein, but there was more in the larger, low-density ("activated") splenic B cells and peritoneal B cells. In vitro Bcl-XL induction following ligation of sIgM-required BTK, was cyclosporin A (CsA)-sensitive and dependent on extracellular Ca2+. CD40-mediated induction of bcl-x required neither wild-type BTK nor extracellular Ca2+ and was insensitive to CsA. These results indicate that BTK lies upstream of bcl-XL in the sIgM but not the CD40 activation pathway. bcl-XL is the first induced protein to be placed downstream of BTK.